Short-term outcomes between laparoscopy-assisted and open colorectomy for colorectal cancer in elderly patients: A case-matched control study - CHEN, ZEXIAN (Mol Clin Oncol, 2015)
With the increase in life expectancy, surgical intervention for colorectal cancer (CRC) is more frequently performed in elderly patients. This retrospective study was designed to compare short-term outcomes between laparoscopy-assisted colorectomy (LC) and open colorectomy (OC) in elderly patients with CRC. A total of 89 CRC patients aged ≥75 years undergoing LC were matched with 89 counterparts undergoing OC. The matching criteria included general information and preoperative status. The operative data and short-term postoperative outcomes were compared. Following analysis, patients in the LC and OC groups were comparable for the matching criteria. Compared with the OC group, the operative time was longer (P=0.046), but the estimated blood loss (P<0.001) and intraoperative transfusion (P=0.042) were less in the LC group. As regards short-term postoperative outcomes, the duration of postoperative hospital stay was shorter (P=0.001) and the incidence of wound complications was lower (P=0.044) with LC. The overall complication, other complications, reoperation and mortality rates were comparable between the two groups. In conclusion, considering the operative variables and short-term outcomes, LC is a safe procedure and appears to be superior to OC for elderly patients with CRC.